IbM PENINGKATAN KESEHATAN BAYI MELALUI MASSAGE BAYI - Lia Dwi Prafitri; Emi Nurlaela (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Public health center Buaran is one of the health facilities in Pekalongan residing in Buaran. Lack of awareness of the mother who has a baby of the importance of infant massage is still a problem in the region Public health center Buaran. Fear and anxiety become one factor causes the mother didn't do baby massage, so there are still many who submit beliefs baby shaman to do baby massage to their babies. Efforts improve health degrees one can do with health promotion. Needed a solution to increase awareness and reduce the anxiety of the mother to be able to do baby massage baby itself to baby's health improved and thus retain its relationship between the mother and her baby. IbM's activities carried out in the region's Public health center Buaran is a village Wonoyoso, village of Watusalam and Simbangkulon Villages. The target in this activity are moms who have babies age 2 months up to 1 year. The results of this activity is on target contributed actively in the activities of baby massage and feel excited to be doing the massage the baby directly to her baby. The resulting external awareness of the importance of infant massage to improve the health of babies.Keywords: Baby Health, Baby Massage